Retirement Consumption: Insights from a Survey - Ameriks, John; Caplin, Andrew; Leahy, John (The Review of Economics and Statistics, 2007)
Prior research has established that consumption falls significantly at retirement. What is not known is the extent to which this fall is anticipated during the working years. Using data from a new survey, we show that many working households do expect a considerable fall in consumption when they retire. In fact, those who are already retired report significantly smaller falls in consumption than are expected by those who are still working.